Psychotherapy in Traditional Society: Context Concepts and Practice - Varma, V. K. Vijoy K.; Gupta, N. Nitin (Jaypee Brothers Medical Publishers, 2008)
Psychotherapy in different cultures carries different meanings. In traditional or socio-centric cultures, the nature of the individual - be it egocentric or socio-centric - will determine what is acceptable in therapy. Furthermore, if the therapist and the patient come from different cultures and have different values, then the therapeutic interaction will become more complex. Issues of race and ethnicity further complicate this matter. Professor Vijoy Varma is ideally placed to bring together different perspectives in psychotherapy across cultures. From the origins of Western psychotherapy to common ingredients of psychotherapy, worldview and emotional charge in these settings to the factors embedded in traditional therapies, Professor Varma highlights the therapy and its implications in economic and social costs and training issues. The role of society and social expectations linked with meditation and use of scriptures in therapy all indicate a broad overview in therapies which deals with all kinds of challenges a psychotherapist is likely to face. With case histories he illustrates components of psychotherapy. It is essential that therapists continue to question their own beliefs but also look at what beliefs and views the patient is holding. This is a remarkable book which will be of interest not only to psychotherapists but also to mental health professionals. This volume should be on the shelf of every therapist.